Atypical hemolytic uremic syndrome triggered by mRNA vaccination against SARS-CoV-2: Case report - Rysava, Romana; Peiskerova, Martina; Tesar, Vladimir; Benes, Jan; Kment, Martin; Szilágyi, Ágnes; Csuka, Dorottya; Prohászka, Zoltán (Frontiers in Immunology, 2022)
Atypical hemolytic uremic syndrome (aHUS), also called complement-mediated hemolytic uremic syndrome (CM-HUS) is a rare disease caused by dysregulation in the alternative complement activation pathway. It is a life-threatening condition causing ischemia of a number of organs and it typically causes acute kidney injury. This disorder may be triggered by various factors including viral or bacterial infections, pregnancy, surgery, injuries etc. In about 60% of cases the genetic origin of the disease can be identified - commonly mutations affecting complementary factor H and MCP protein. Eculizumab, a monoclonal antibody to the C5 component of the complement, represents the current effective treatment. We describe a case of a young woman with a previous history of polyvalent allergies, who developed atypical hemolytic uremic syndrome after vaccination with mRNA vaccine against SARS-CoV2. The disease manifested by scleral bleeding, acute renal insufficiency, anemia, thrombocytopenia. The patient was treated with plasmapheresis without sufficient effect, remission occurred only after starting treatment with eculizumab. Genetic examination showed that the patient is a carrier of multiple inherited risk factors (a rare pathogenic variant in CFH, MCPggaac haplotype of the CD46 gene, the risk haplotype CFH H3). The patient is currently in hematological remission with persistent mild renal insufficiency, continuing treatment with eculizumab/ravulizumab. By this case report we meant to point out the need for careful monitoring of people after vaccination, as it may trigger immune-mediated diseases, especially in those with predisposing factors.